2020
DOI: 10.1007/s00701-020-04423-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms behind altered pulsatile intracranial pressure in idiopathic normal pressure hydrocephalus: role of vascular pulsatility and systemic hemodynamic variables

Abstract: Background The dementia subtype idiopathic normal pressure hydrocephalus (iNPH) has unknown etiology, but one characteristic is elevated intracranial pressure (ICP) wave amplitudes in those individuals who respond with clinical improvement following cerebrospinal fluid (CSF) diversion. To explore the mechanisms behind altered ICP wave amplitudes, we correlated central aortic blood pressure (BP) and ICP waveform amplitudes (intracranial aortic amplitude correlation) and examined how this correlation relates to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, experiments intending to prove the magnitude of this pulsatile effect through the aqueduct have found this effect to be too small for considerable efficacy (Holmlund et al., 2019). Although ICP overnight measurements in patients with iNPH have shown a normal amplitude pressure level, a higher pulsatility has been reported underlying the assumed mechanism, contradictory to the above cited observations (Evensen & Eide, 2020). Today, diagnostic workup mainly consists of tapping 30–40 ml CSF by lumbar puncture, simulating shunt therapy.…”
Section: Disorders Of Csf and The Astrocytic Networkmentioning
confidence: 71%
“…However, experiments intending to prove the magnitude of this pulsatile effect through the aqueduct have found this effect to be too small for considerable efficacy (Holmlund et al., 2019). Although ICP overnight measurements in patients with iNPH have shown a normal amplitude pressure level, a higher pulsatility has been reported underlying the assumed mechanism, contradictory to the above cited observations (Evensen & Eide, 2020). Today, diagnostic workup mainly consists of tapping 30–40 ml CSF by lumbar puncture, simulating shunt therapy.…”
Section: Disorders Of Csf and The Astrocytic Networkmentioning
confidence: 71%
“…In previous studies, we found that high correlation between intracranial and vascular pressure pulsatility in patients with subarachnoid hemorrhage was accompanied with worse outcome 34 . In subjects with iNPH, there was low correlation between intracranial and vascular pressure pulsatility in the majority of patients 35 . We suggest that elevated intracranial pulsatility due to underlying disease causes restriction on the arterial pulsatility, which in turn hampers the perivascular tracer transport.…”
Section: Discussionmentioning
confidence: 85%
“…ICP monitoring, initially introduced by Lundberg [ 3 ], has been used for diagnosing and managing different brain diseases, such as hydrocephalus, idiopathic intracranial hypertension, traumatic brain injury, and cerebral haemorrhages [ 4 – 6 ]. Currently, only the mean ICP value is considered in clinical practice; however, a growing number of researchers are interested in studying the shape of the ICP pulse waveform [ 7 – 9 ] to better understand the pathology’s origin [ 10 ]. Typically, the ICP pulse is composed of three peaks, P1, P2, and P3, which in healthy cases, P1 predominates in amplitude over P2 and P3 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%